Adaptive Fuzzy Control for Path Tracking of Underactuated Ships Based on Dynamic Equilibrium State Theory - Dehui Qiu; Qinglin Wang; Jie Yang; Jinhua She (International Journal of Computational Intelligence Systems, 2011)
This paper presents an adaptive fuzzy backstepping control method that incorporates the dynamic equilibrium state (DES) theory to carry out path tracking for underactuated ships in presence of parameter variations and external disturbances induced by wind, wave and current. First, the optimal DES reference trajectories are designed for the sway displacement and the yaw angle. Then, by combining the DES theory with backstepping technology and using fuzzy logic systems to approximate unknown nonlinear functions in the system, a robust adaptive fuzzy controller is designed to track the prescribed trajectories. Theoretical analysis and simulation results show that the proposed method performs path tracking of underactuated ships with high precision, eliminates the influence of the uncertainties, and guarantees global stability and robustness of the system.